“Strengthening the faith of the children of God": Pietism, print, and prayer in the making of a world evangelical hero, George Müller of Bristol (1805-1898) - Lenz, Darin Duane (Kansas State University, 2010)
George Müller of Bristol (1805-1898) was widely celebrated in the nineteenth century as the founder of the Ashley Down Orphan Homes in Bristol, England. He was a German immigrant to Great Britain who was at the vanguard of evangelical philanthropic care of children. The object of his charitable work, orphans, influenced the establishment of Christian orphanages in Great Britain, North America, Asia, Africa, Latin America, and Europe. However, what brought Müller widespread public acclaim was his assertion that he supported his orphan homes solely by relying on faith and prayer. According to Müller, he prayed to God for the material needs of the orphans and he believed, in faith, that those needs were supplied by God, without resort to direct solicitation, through donations given to him. He employed his method as a means to strengthen the faith of his fellow Christians and published an ongoing chronicle of his answered prayers that served as evidence. Müller’s method of financial support brought him to the forefront of public debate in the nineteenth century about the efficacy of prayer and the supernatural claims of Christianity. His use of prayer to provide for the orphans made his name a “household word the world round.” This dissertation is a study of Müller’s influence on evangelicals that analyzes Müller’s enduring legacy as a hero of the faith among evangelicals around the world. For evangelicals Müller was an exemplary Christian—a Protestant saint—who embodied a simple but pure form of biblical piety. To explore his influence from the nineteenth century through the twentieth century, this study, as a social biography, investigates how evangelicals remember individuals and how that memory, in this case Müller, influenced the practice of prayer in evangelical piety. The dissertation affirms a link between evangelicals and eighteenth-century German Pietism, while also showing that evangelicals used publications to celebrate and to informally canonize individuals esteemed for their piety. The dissertation, ultimately, is concerned with how evangelicals identified heroes of the faith and why these heroes were and are widely used as models for edification and for emulation in everyday life.
Keywords: George Müller; Pietism; Evangelicalism; Protestant saints; 19th-century philanthropy; World Christianity; History, Church (0330)